Difficulties of Implementing Continuous Assessment in Physical Education Classes in Certain Secondary Schools in Eastern Algeria. - Ahmed, ROUINI; Tarek, KHALLAFI (Journal of Sport Science Technology and Physical Activities, 2026)
This study investigates the main challenges faced by physical education teachers in implementing continuous assessment during secondary school classes in eastern Algeria. The research employed a descriptive survey method, targeting a simple random sample of 364 physical education teachers distributed across 20 education directorates in the eastern region. Data were collected using a questionnaire consisting of five axes, each containing 12 items, designed to capture a comprehensive understanding of the difficulties encountered. Statistical analysis involved calculating correlation coefficients, Cronbach’s alpha, means, and standard deviations to ensure the reliability and validity of findings. The results reveal that the lack of adequate facilities and equipment stands as the foremost challenge hindering effective continuous assessment. This is followed by issues related to scheduling and limited class time, then by student characteristics. The scientific content of the curriculum and teacher-related factors were found to pose lesser difficulties, respectively.